2021
DOI: 10.1021/jacs.1c00476
|View full text |Cite
|
Sign up to set email alerts
|

meso-Oxoisocorroles: Tunable Antiaromaticity by Metalation and Coordination of Lewis Acids as Well as Aromaticity Reversal in the Triplet Excited State

Abstract: The corrole derivative meso-oxoisocorrole has been theoretically predicted to be antiaromatic, despite its formally cross conjugated electronic system. In this study, this prediction has been experimentally proven by the facile preparation of meso-oxoisocorrole via the oxidation of a meso free corrole with MnO2 and its comprehensive characterization using NMR, UV/vis absorption, FT-IR, and transient-absorption spectroscopy, cyclic voltammetry, and X-ray diffraction analysis. Furthermore, the free base meso-oxo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 65 publications
1
19
0
Order By: Relevance
“…The parent ion peak of 11 was observed at m/z =701.0238, calcd for (C 32 H 22 BBr 2 F 2 N 5 O)=701.0234 ([M] + ), The 1 H NMR spectrum of 11 exhibits signals due to the pyrrolic β ‐protons in a range of 6.88‐5.74 ppm, a singlet at 5.61 ppm due to the meso ‐proton, two signals at 18.67 and 18.29 ppm due to the inner pyrrolic NH‐protons. These chemical shifts suggest weak antiaromatic character for 11 [8] . NICS(0) value of 8.210 in the center of the smaragdyrin core and a HOMA value of 0.584 further prove its weak antiaromaticity.…”
Section: Methodsmentioning
confidence: 77%
See 1 more Smart Citation
“…The parent ion peak of 11 was observed at m/z =701.0238, calcd for (C 32 H 22 BBr 2 F 2 N 5 O)=701.0234 ([M] + ), The 1 H NMR spectrum of 11 exhibits signals due to the pyrrolic β ‐protons in a range of 6.88‐5.74 ppm, a singlet at 5.61 ppm due to the meso ‐proton, two signals at 18.67 and 18.29 ppm due to the inner pyrrolic NH‐protons. These chemical shifts suggest weak antiaromatic character for 11 [8] . NICS(0) value of 8.210 in the center of the smaragdyrin core and a HOMA value of 0.584 further prove its weak antiaromaticity.…”
Section: Methodsmentioning
confidence: 77%
“…These chemical shifts suggest weak antiaromatic character for 11. [8] NICS(0) value of 8.210 in the center of the smaragdyrin core and a HOMA value of 0.584 further prove its weak antiaromaticity. As a comparison 10 shows a NICS(0) value of À 14.488 in the center of the smaragdyrin core and a HOMA value of 0.802, suggesting it an aromatic molecule (see the supporting information).…”
mentioning
confidence: 84%
“…Tropone and its derivatives, such as tropolone, 11 c are pseudoaromatic compounds. Carbonyl-substituted meso -oxoisocorroles have been recently reported to enhance their antiaromaticity in the presence of Lewis acids, 21 as predicted by the DFT calculations. 22 Thus, when the global 24π antiaromaticity of homoHPHACs was not observed clearly for their neutral states even in polar solvents, Lewis acid or alkylation reagents were added to enhance or force the CO or CS polarisation.…”
mentioning
confidence: 68%
“…In particular, the realization of antiaromaticity has received considerable attention on account of the drastic change it induces in the electronic nature of a system. The switching of the aromaticity/antiaromaticity in nitrogen‐containing macrocyclic π‐systems is often achieved by conformational changes through protonation and temperature changes [20–27] . Sessler and co‐workers have reported that cyclo[2]pyridine[4]pyrrole is converted from its neutral nonaromatic state to the 24π antiaromatic state upon protonation of the pyridinic nitrogen atoms due to delocalization of the positive charges (Figure 1d) [28] .…”
Section: Introductionmentioning
confidence: 99%
“…The switching of the aromaticity/antiaromaticity in nitrogen-containing macro-cyclic π-systems is often achieved by conformational changes through protonation and temperature changes. [20][21][22][23][24][25][26][27] Sessler and co-workers have reported that cyclo [2]pyridine [4]pyrrole is converted from its neutral nonaromatic state to the 24π antiaromatic state upon protonation of the pyridinic nitrogen atoms due to delocalization of the positive charges (Figure 1d). [28] However, the use of such strategies to control electronic properties has been limited to a few examples of porphyrinoids.…”
Section: Introductionmentioning
confidence: 99%